2022
DOI: 10.1002/acn3.51512
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of systemic inflammation and brain iron deposition in Parkinson's disease patients

Abstract: measurement, the Home for Researchers editorial team for the language polishment (www.home-for-researchers.com).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…IL‐1β levels in the CSF were positively correlated with brain iron deposition detected by susceptibility weighted image (SWI) (Liu et al, 2017). In addition, there was an association between serum IL‐1β concentrations and iron deposition measured by quantitative susceptibility mapping (QSM) (Xu et al, 2022). What is more, it has been reported from animal studies that microglial activation is associated with increased ferritin expression and iron deposition in the SN (Hunter et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…IL‐1β levels in the CSF were positively correlated with brain iron deposition detected by susceptibility weighted image (SWI) (Liu et al, 2017). In addition, there was an association between serum IL‐1β concentrations and iron deposition measured by quantitative susceptibility mapping (QSM) (Xu et al, 2022). What is more, it has been reported from animal studies that microglial activation is associated with increased ferritin expression and iron deposition in the SN (Hunter et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found elevated concentrations of IL-33 in serum and midbrain and striatum in PD groups, and IL-33 enhances glial maturation factor (GMF)-mediated neuroinflammation [ 134 , 135 ]. In addition, Xu et al found that serum IL33 concentrations were higher in early PD patients than in late [ 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…Iron is one of the common biological essential trace elements, which plays many critical cellular functions in all organisms while catalyzing the formation of potentially toxic free radicals. A large body of evidence substantiates the potential additive effect of oxidative stress as iron stores increase, further exacerbating disease susceptibility and responses to infection and inflammation ( 46 , 47 ). The observed increase in iron concentration with C-DII in our study suggests that an inflammatory diet may lead to inflammatory oxidative stress in the body (especially the liver).…”
Section: Discussionmentioning
confidence: 99%